Awarding of green coffee bean (Coffea arabica) extract improved lipid profile in dyslypidemic male wistar rats (Rattus norvegicus) - Fibriany Chandra; I Wayan Weta; Ni Nyoman Ayu Dewi (Fakultas Kedokteran Universitas Udayana, 2021)
Introduction: Dyslipidemia is a lipid metabolic disorder characterized by increased or decreased lipid fraction in plasma. The active compounds of chlorogenic acid in coffee can increases the body’s metabolism, increases fatty acid oxidation, decreases triglyceride levels in the liver, and inhibit the action of the enzyme amylase and lipase pancreas in the intestinal. This study aimed to prove the effectiveness of green coffee bean extract in improving serum lipid profile levels in dyslipidemic male Wistar rats. Methods: The research design was experimental pre-post test control group using 14 male Wistar rats. The control group was given placebo (2 cc aquades), while the second group was treated with ethanol extract of green beans dose 200 mg/kg dissolved in 2 cc aquades given sonde with treatment time of 14 days. On the first and fifteenth days, blood sampling is done to check the lipid profile level. Results: The results showed that the mean total cholesterol level of the control group was 137.86 ± 10.12 mg/dL while the total cholesterol level in the treatment group was 137.86 ± 10.12 mg/dL. The mean of triglyceride level, LDL level, and HDL level control group was 100.86 ± 8.98 mg/dL, 97.57 ± 4.65 mg/dL, and 51.57 ± 4.96 mg/dL while triglyceride level, LDL level, and HDL level in treatment group was 76.86 ± 4.94 mg/dL, 82.86 ± 5.21 mg/dL and 66.43 ± 8.84 mg/dL. Conclusion: Arabica green coffee bean (Coffea arabica) extract improves the lipid profile of dyslipidemic male Wistar rats (Rattus norvegicus).